Self-concept and communication skills: a focus among UTM final year tesl students - Rajab, Azizah; Che Abas, Atirah Izzah (2010)
The purposes of this study were to identify the levels of communication skills and the levels of self-concept among the UTM final year TESL students as well as to identify the relationship between these two variables. The scope of the communication skills was based on the skills evident during the MUET speaking examination. Five components were used for the self-concept variables namely physical self, moral-ethical self, personal self, family self and lastly social self. The sample consisted of 33 final year TESL students from Universiti Teknologi Malaysia where two instruments were used to measure their levels of communication skills and their levels of self-concept. MUET speaking skill scores were used to measure the respondents’ levels of communication skills while Tennessee Self-Concept Scale Test (1965) was used to measure their levels of self-concept. A number of statistical analyses were employed in order to analyze the data including descriptive statistics, one-way ANOVA and Pearson correlation. From this research it was found that the majority of the final year TESL students possess high level of communication skills and high level of self-concept. The Pearson correlation revealed that there was no significant correlation between the respondents’ self-concept and communication skills. In conclusion, this research investigates the influence of self-concept in the final year TESL students’ communication skills.